Microscopic intramural extension of rectal cancer after neoadjuvant chemoradiation: A meta-analysis based on individual patient data. (March 2020) - Verrijssen, An-Sofie; Guillem, José; Perez, Rodrigo; Bujko, Krzysztof; Guedj, Nathalie; Habr-Gama, Angelita; Houben, Ruud; Goudkade, Danny; Melenhorst, Jarno; Buijsen, Jeroen; Vanneste, Ben; Grabsch, Heike I.; et al.
Highlights: This data can be used to determine margins for radiotherapy boosting for rectal cancer. 80% of rectal tumors showed no microscopic intramural spread after neoadjuvant chemoradiation. To treat all MIS in 95% of patients, a 5.5 mm margin around visible residual tumor would suffice. Exploratory analysis showed that ypT stage was predictive for extent of MIS. Exploratory analysis showed: longer interval between chemoradiation and surgery gives more MIS. Abstract: Objective: In selected rectal cancer patients with residual local disease following neoadjuvant chemoradiation (CRT) and the preference of an organ preservation pathway, additional treatment with dose escalation by endoluminal radiotherapy (RT) may ultimately result in a clinical complete response. To date, the widespread introduction of selective endoluminal radiation techniques is hampered by a lack of evidence-based guidelines that describe the radiation treatment volume in relation to the residual tumor mass. In order to convert an incomplete response into a complete one with additional treatment such as dose-escalation with endoluminal RT from a theoretical perspective, it seems important to treat all remaining microscopic tumor cells after CRT. In this setting, residual tumor extension beneath normal appearing mucosa (microscopic intramural spread – MIS) becomes relevant for accurate tumor volume and margin estimation. With the goal of providing evidence-based guidelines that define an appropriate treatment volume and patient selection, we present results from a meta-analysis based on individual patient data of studies that have assessed the extent or range of MIS of rectal cancers after neoadjuvant CRT. This meta-analysis should provide an estimate of the residual tumor volume/extension that needs to be targeted by any additional radiation therapy boost in order to achieve complete tumor eradication after initial incomplete or near-complete response following standard CRT. Methods and materials: A PubMed search was performed. Additional articles were selected based on identification from reference lists. Papers were eligible when reporting MIS in patients who were treated by total mesorectal excision or local excision/transanal endoscopic microsurgery (TEM) after neo-adjuvant long-course CRT. The mean MIS was calculated for the entire group along with the 70th until 95th percentiles. Additional exploratory subgroup analyses were performed. Results: Individual patient data from 349 patients with residual disease from five studies were analyzed. 80% of tumors showed no MIS. In order to appropriately treat MIS in 95% of rectal cancer patients after CRT, a margin of 5.5 mm around the macroscopic tumor would suffice. An exploratory subgroup analysis showed that T-stage after CRT (ypT) and time interval between neoadjuvant CRT and surgery are significant factors predicting the extent of MIS ( p  < 0.001.) The group of ypT1 had the smallest MIS, followed by the ypT3-4 group, while the ypT2 group had the largest MIS ( p  < 0.001). Regarding time interval between CRT and surgery, a statistically significant difference was seen when comparing the three time-interval groups (less than 8 weeks, 8–12 weeks, and more than 12 weeks), where waiting more than 12 weeks after CRT resulted in the largest MIS ( p  < 0.0001). Conclusion: Based on this meta-analysis, in order to treat the MIS for 95% of rectal cancer patients after CRT, a Clinical Target Volume (CTV) margin of 5.5 mm from the lateral most edge of the macroscopic tumor would suffice. 80% of tumors showed no MIS and would not require an extra CTV margin for treatment. These findings support the feasibility of localized radiotherapy boosts for dose-escalation to improve response among patients with incomplete response after standard CRT and can also be applied in the surgical setting.